Insight into Sexual Risk Reduction for College-Entering Males Reacting to Gender-Tailored Role Play Scenarios - Allison Lazor; Dianne Morrison-Beedy (The Ohio State University Libraries, 2022)
Background: College represents a time of independent decision making, increased exposure to substances, and new, less supervised, opportunities for sexual behaviors and new partners. Despite the high prevalence of sexual risk behaviors in adolescent males pursuing higher education, there are still limited evidence-based interventions for sexually transmitted infections (STI), human immunodeficiency virus (HIV), and pregnancy prevention tailored for this population. Aim: The aim of this study was to gain insight into the perspectives of males on role play situations used in a sexual risk reduction program tailored for adolescent girls to obtain feedback on creating effective prevention programs for males. Methods: We conducted a focus group with males entering college. We analyzed the transcribed data to assess the relevance, realism, and utility of role-playing and to gain insight into the participant's communication styles and approaches to risk reduction. Results: Four major themes were identified using conventional content analysis: (1) Non-verbal responses and "the vibe" are the go ahead for consent for sex, (2) Jokes and excuses are common communication skills used for risk reduction, (3) Prevention of pregnancy is more of a concern than STI or HIV prevention, and (4) Being gaslighted regarding mental health issues by girls was not uncommon. Conclusions: Findings from this pilot study can help inform sexual risk reduction intervention programming for males entering new environments such as the college-setting.